Seasonal patterns of vocal mimicry in northern mockingbirds Mimus polyglottos. (9th July 2014) - Gammon, David E.
<x xml:space="preserve">Abstract</x> Many aspects of birdsong vary seasonally, but we know almost nothing about seasonal variation in vocal mimicry, a conspicuous feature of the songs of 15–20% of bird species. I sampled spontaneous song from nine, free‐living, male northern mockingbirds Mimus polyglottos four times during the calendar year – three times during the breeding season, and once during the non‐breeding season. Results showed that mockingbirds did not mimic summer migrants significantly more during any sampling period. Results also showed significant differences across sampling periods in the frequency, but not diversity, of mimicry. Frequency of mimicry was highest in late spring (61.3%) and lowest during the non‐breeding season (48.3%), suggesting mimicry might play a role in reproductive stimulation of multiple‐brooded females. Because mockingbirds mimicked summer migrants throughout the year, regardless of whether migrants were present, mimicry is unlikely to facilitate interspecies communication. Seasonal patterns also suggest that females might be attracted to a high frequency of mimicry, but not to a high diversity of mimicry. I argue that observational studies of seasonal variation in additional mimics could provide key insights into the functional role of vocal mimicry.